Legal Reconstruction in Risk-Based Business Licensing Procedures for Indonesia’s Economic Growth - Kunarto, Kunarto; Jha, Gautam Kumar (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2022)
Economic development is the most important thing in the nation’s progress because the community’s welfare is one indicator of the success of the development. Therefore, one of the government’s efforts in economic development is to prepare good legal instruments in the form of licensing regulations. Licensing is an instrument of government policy to control negative externalizations that social and economic activities may cause. Through Government Regulation No. 24 of 2018 concerning Electronically Integrated Business Licensing Services, all forms of business, including in the regions, must go through the OSS system. However, there are still many problems in its implementation. This paper describes the implementation of risk-based licensing through the OSS system in growing the Indonesian economy. In addition, this paper will describe the challenges, obstacles, and solutions to overcome these problems. The results showed that implementing risk-based licensing through the OSS system went well and received a positive response from the community, especially business actors. Online-based licensing management can reduce time, cost, and effort. Then to overcome these obstacles, the government continues to strive and improve, including monitoring, infrastructure development, mentoring, and enhancing human resources.